Cerebral blood flow and personality: a positron emission tomography study. - Johnson, Debra L.; Wiebe, John S.; Gold, Sherri M. (American Journal of Psychiatry, 1999)
|WbObjective:[|WB] This study sought to describe brain regions associated with the personality dimension of introversion/extraversion. |WbMethod:[|WB] Measures of cerebral blood flow (CBF) were obtained from 18 healthy subjects by means of {15O}H2O positron emission tomography. Correlations of regional CBF with introversion/extraversion were calculated, and a three-dimensional map of those correlations was generated. |WbResults:[|WB] Overall, introversion was associated with increased blood flow in the frontal lobes and in the anterior thalamus. Regions in the anterior cingulate gyrus, the temporal lobes, and the posterior thalamus were found to be correlated with extraversion. |WbConclusions:[|WB] The findings of the study lend support to the notion that introversion is associated with increased activity in frontal lobe regions. Moreover, the study suggests that individual differences in introversion and extraversion are related to differences in a fronto-striato-thalamic circuit. Reprinted by permission of the publisher.